2002
DOI: 10.1063/1.1436279
|View full text |Cite
|
Sign up to set email alerts
|

GaN metal–oxide–semiconductor structures using Ga-oxide dielectrics formed by photoelectrochemical oxidation

Abstract: GaN metal–oxide–semiconductor (MOS) capacitors were fabricated by using Ga oxide formed by photoelectrochemical oxidation of GaN. The electrical properties of the MOS structures as characterized by capacitance–voltage measurement were found to be dependent on the oxidation time and posttreatment. Positive flatband voltage was observed in devices with thin oxide layers indicating the existence of negative oxide charge. Very thin oxide exhibits high capacitance and reverse leakage, which can be reduced by rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 16 publications
0
8
2
Order By: Relevance
“…4. Compared to Ga 2 O 3 on GaN reported by Fu et al, 16 the D it of our photo-CVD SiO 2 prepared at 300°C on GaN was one order smaller. It was found that no significant hysteretic curve could be observed as the gate voltage varied from ϩ5 V to Ϫ20 V and then back to ϩ5 V for all three samples even at an elevated temperature of 70°C.…”
Section: Characteristics Of Al/sio 2 /Gan Metal-insulator Semiconductcontrasting
confidence: 78%
“…4. Compared to Ga 2 O 3 on GaN reported by Fu et al, 16 the D it of our photo-CVD SiO 2 prepared at 300°C on GaN was one order smaller. It was found that no significant hysteretic curve could be observed as the gate voltage varied from ϩ5 V to Ϫ20 V and then back to ϩ5 V for all three samples even at an elevated temperature of 70°C.…”
Section: Characteristics Of Al/sio 2 /Gan Metal-insulator Semiconductcontrasting
confidence: 78%
“…The XAS spectra for the same sample acquired in a surfacesensitive mode identifies the Ga signal to be in an oxidized state which is further confirmed by the HAXPES and XAS spectra following the 400°C anneal, where the Ga oxide is identified as Ga 2 O 3 . It is likely that oxidized Ga seen in the 20°C spectra is composed of a number of suboxide states, and following anneal at 400°C the greater concentration of Ga at the Ni-(In,Ga)As surface forms Ga 2 O 3 , which is the most stable of the Ga oxides [39].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can be natively grown on GaN by thermal or chemical processing [48,49]. Therefore, foreign contaminants can be avoided in the oxide/GaN [48,49,52]. Of the processing methods, thermal oxidation with relatively cheaper cost and simple process is usually a desirable technique to produce Ga 2 O 3 on GaN [1,4,21].…”
Section: Introductionmentioning
confidence: 99%
“…It is a stable native oxide of GaN with the band gap of 4.8 eV, dielectric constant of 10.2e14.2, thermal and chemical stability [9,48e51]. Moreover, it can be natively grown on GaN by thermal or chemical processing [48,49]. Therefore, foreign contaminants can be avoided in the oxide/GaN [48,49,52].…”
Section: Introductionmentioning
confidence: 99%